Reconstruction Of Tax Criminal Law Enforcement Based On Digital Transformation: A Juridical And Economic Review To Strengthen National Stability - Nur Hakim; Yuhelson (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Tax crimes constitute a fundamental threat to fiscal sovereignty, as they distort the stability of the national economy. This study examines the urgency of reconstructing the tax criminal law enforcement system, which currently faces increasingly complex challenges arising from cross-border modus operandi, including the manipulation of transfer pricing and the abuse of tax havens. Employing a juridical-normative research method combined with the economic analysis of law, this study evaluates the weaknesses of the existing regulatory framework in responding to the rapid digitalization of global financial transactions. The findings reveal that the disparity between conventional regulatory mechanisms and the growing sophistication of tax crime schemes has resulted in significant leakage of state revenue. Accordingly, a legal reconstruction is required that places digital transformation including the integration of Big Data analytics, the Automatic Exchange of Information (AEOI), and digital forensics as the principal foundation of the tax monitoring and criminal evidentiary system. This reconstruction aims to establish legal certainty grounded in justice, while simultaneously optimizing state financial loss recovery through asset recovery mechanisms, thereby strengthening national resilience and stability.